'Faith in God and the last day' in Ghazālī: What Faith for What People?. (25th April 2022) - Leites, Adrien
Abstract: This article considers the use of the traditional phrase 'faith in God and the last day' in five shorter works of Abū Ḥāmid al-Ghazālī. It looks into Ghazālī's understanding of the 'minimal faith' specified by this phrase, and makes three main points. Ghazālī regards minimal faith as having a synthetic object, which may be called 'a retributory God' or simply 'otherworldly retribution'. Minimal faith as understood by Ghazālī is useful to bring deficient Muslims back to observance. Ghazālī also regards minimal faith as useful to make non-Muslims shift to Islam, but does not regard this faith as shared specifically by Jews and Christians. The rhetorical and polemical trend of Ghazālī, on the other hand, is presented in the course of the article. Ghazālī's concern with persuading or discrediting, I eventually argue, might outweigh his involvement in 'doctrine'.